E-Learning in Developing Countries: Is it a Panacea? A Case Study of Sudan - Mohd Elmagzoub Eltahir (IEEE Access, 2019)
Despite the increasing costs of education and the growing use of information communication technologies (ICTs) in developing countries, the need for more educational opportunities is increasing. This paper aims to answer the question: is e-learning a panacea for education in developing countries? It is based on the case country Sudan, and analyzes students', academics', and policymakers' attitudes toward e-learning, ICTs, and educational technology. This study uses an exploratory research approach, and relies mainly on two data collection instruments: questionnaire and semi-structured interview. A survey was conducted on a population of academics and students at five public universities in Sudan, as well as policymakers from these institutions and the higher education ministry. A convenience sample of 400 was chosen as the target population representation. A total of 388 valid questionnaires were returned. The results show more conservative attitudes toward e-learning and ICTs among academics and policymakers. The study concludes that there is an increasing demand in developing countries for more authentic learning opportunities and simulated experiences that the e-learning can provide. E-learning, however, is a paradigm entirely different from traditional face-to-face education. To do e-learning work, a different roles and practice is required for the educator.